Unmasking a hidden culprit: a case of 'diphtheritic' colitis - Zainulabid, Ummu Afeera; Jaafar, Khairul Azhar; Che Aun, Azlida; Periyasamy, Petrick (2023)
Pseudomembranous colitis, originally referred to as "diphtheritic colitis" by Finney in the late 1800s, has transformed from a fatal postoperative complication to a prevalent complication of antibiotic use that can lead to severe morbidity. This case report presents a complicated situation of a 71-year-old female patient diagnosed with colorectal carcinoma who developed pseudomembranous colitis after undergoing multiple rounds of antibiotics and chemotherapy. Despite treatment for acute infectious gastroenteritis, she exhibited no improvement. She was later diagnosed with pseudomembranous colitis after a colonoscopy revealing yellow raised lesions on edematous and erythematous mucosa. The patient was successfully treated with a 10-day oral vancomycin course without further relapse. Risk factors for pseudomembranous colitis include previous antibiotic use, treatment with proton pump inhibitors, nonsteroidal anti-inflammatory drugs, corticosteroids, and chemotherapy. Management of nosocomial diarrhea requires various diagnostic tests to determine the best course of action as Clostridium difficile infection, a common cause of pseudomembranous colitis, can cause a range of symptoms.